2013
DOI: 10.1242/jcs.139725
|View full text |Cite
|
Sign up to set email alerts
|

A minimal number of MELT repeats supports all functions of KNL1 in chromosome segregation

Abstract: The Bub1-Bub3 and BubR1-Bub3 checkpoint complexes, or the Bubs, contribute to the accurate segregation of chromosomes during mitosis by promoting chromosome bi-orientation and halting exit from mitosis if this fails. The complexes associate with kinetochores during mitosis, which is required for proper chromosome segregation. The outer kinetochore protein KNL1 (also known as CASC5, Blinkin and AF15Q14) is the receptor for Bub proteins, but the exact nature of the functional binding sites on KNL1 are yet to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
155
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(165 citation statements)
references
References 43 publications
9
155
1
Order By: Relevance
“…In C. elegans, PP1 binding to Knl1 plays a role in SAC silencing, which might ensure the timely removal of Bub1 and BubR1 from the kinetochore (Espeut et al, 2012). In agreement with this, the Nilsson laboratory recently reported that deletion of the first 150 or 300 amino acids of Knl1, or the mutation of the Nterminal Knl1 PP1-binding site, results in increased levels of Bub1 and BubR1 at the kinetochore compared with that in cells expressing wild-type Knl1, suggesting that PP1 negatively regulates the recruitment of Bub1 and BubR1 (Zhang et al, 2014;London et al, 2012;Meadows et al, 2011;Rosenberg et al, 2011). In addition to PP1, Knl1 indirectly mediates the recruitment of PP2A through the recruitment of BubR1, which binds directly to the B56 family of PP2A regulatory subunits (Suijkerbuijk et al, 2012;Kruse et al, 2013;Xu et al, 2013).…”
Section: Knl1 Protein-interacting Regions Silk and Rvsf Motifsmentioning
confidence: 63%
See 2 more Smart Citations
“…In C. elegans, PP1 binding to Knl1 plays a role in SAC silencing, which might ensure the timely removal of Bub1 and BubR1 from the kinetochore (Espeut et al, 2012). In agreement with this, the Nilsson laboratory recently reported that deletion of the first 150 or 300 amino acids of Knl1, or the mutation of the Nterminal Knl1 PP1-binding site, results in increased levels of Bub1 and BubR1 at the kinetochore compared with that in cells expressing wild-type Knl1, suggesting that PP1 negatively regulates the recruitment of Bub1 and BubR1 (Zhang et al, 2014;London et al, 2012;Meadows et al, 2011;Rosenberg et al, 2011). In addition to PP1, Knl1 indirectly mediates the recruitment of PP2A through the recruitment of BubR1, which binds directly to the B56 family of PP2A regulatory subunits (Suijkerbuijk et al, 2012;Kruse et al, 2013;Xu et al, 2013).…”
Section: Knl1 Protein-interacting Regions Silk and Rvsf Motifsmentioning
confidence: 63%
“…Structural and biochemical evidence has demonstrated that phosphorylated MELT motifs bind directly and with high affinity to Bub3 (Primorac et al, 2013;Zhang et al, 2014). The crystal structure of Bub3 from budding yeast in complex with a synthetic MELT phosphopeptide and the Bub3-binding region of Bub1 (a protein motif commonly referred to as the GLEBS motif) identified a well-conserved region on the side of the b-propeller structure that is formed by the Bub3 WD40 repeats (Box 2) as the site that binds to the phosphorylated MELT motif (Primorac et al, 2013; Fig.…”
Section: Knl1 Protein-interacting Regions Silk and Rvsf Motifsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been speculated that since binding affinity of BUB1:BUB3 to an individual MELT P is very high, each MELT repeat can potentially recruit a BUB1:BUB3 complex and therefore multiple BUB1:BUB3 complexes can concurrently bind to multiple MELT P repeats at a given time. 23,24,30 Variations in the level of phosphorylation of different active repeats is likely to function as a governing factor or may provide a subtle layer of regulation in controlling the strength of SAC response but this hypothesis needs to be substantiated experimentally. In addition, the MELT repeats function cooperatively with the 2 N-terminally located, 10-12 amino acids long, and closely related yet distinct KI (LysIle) motifs, KI1 (KIDTTSFLANLK) and KI2 (KIDFNDFIKRLK) to directly recruit BUB1 and BUBR1, respectively, by binding to their tetratricopeptide repeat (TPR) domains to ensure robust SAC activity (Fig.…”
Section: The Ndc80 Complexmentioning
confidence: 99%
“…When phosphorylated, these motifs recruit BUB1-BUB3 dimers that are essential for SAC signaling and chromosome bi-orientation (Krenn et al, 2014;Primorac et al, 2013;Vleugel et al, 2013Vleugel et al, , 2015Zhang et al, 2014). Since the discovery of BUB1, the molecular mechanism by which it participates in SAC activation has been a matter of controversy.…”
Section: Introductionmentioning
confidence: 99%